Tratamento ambulatorial da endocardite estreptocócica - Hassem Sobrinho, Sírio (2010)
Bacterial endocarditis is a serious infectious disease, the treatment of which is traditionally performed with the patient hospitalized and receiving intravenous medication. When the etiological agent is Streptococcus, progression is generally less aggressive. Thus, the possibility of outpatient treatment becomes an attractive option from the social and economic standpoint. In the literature, this type of treatment is known as outpatient parenteral antimicrobial therapy (OPAT). Objective: The aim of the present study was to demonstrate that outpatient treatment is safe and effective in cases of streptococcic endocarditis. Patients and Methods: Six patients with bacterial endocarditis, diagnosed using the modified Duke University criteria, were followed up between January 2006 and November 2008. Four patients were female (66.6%) and two were male (33.4%). Mean age was 47.8 years, ranging from 32 to 65 years. All patients were eligible for outpatient treatment and agreed to take part in the study, having been either partially or wholly treated in an outpatient regimen. xiii Imaging and laboratory exams were performed at the beginning and end of treatment and when otherwise deemed necessary. Results: All patients progressed with no complications and with the complete resolution of the infection. The results of the laboratory and imaging exams are presented and discussed. Conclusion: Streptococcic bacterial endocarditis may be safely and effectively treated in an outpatient regimen for selected patients with no concomitant aggravating factors.